Comparison of Mature, Immature, and Neurotic Defense Mechanisms in Veterans and Normal People - R. Kazemian; Kh. Abolmaali Alhosseini (Afarand Scholarly Publishing Institute, 2018)
Aims: The stresses and fears experienced by veterans affect their use of defense mechanisms. The aim of this study was to compare the mature, immature, and neurotic defense mechanisms in veterans and normal people.  Instruments and Methods: In the present causal-comparative retrospective study, the statistical population included veterans supported by the Martyr Foundation and Issargaran affairs in Tehran 1395, and normal people over the age of 25 living in Tehran. In this study, 40 veterans were selected from Sarallah Rehabilitation Hospital, Sadr Psychiatric Hospital, and Niyayesh Psychiatric Hospital and 40 normal people were selected from the husbands of female students of the Center for Behavioral Cognition by convenience sampling method. The Defense Style Questionnaire was used as a research tool and the data were analyzed by SPSS 22 software through multivariate analysis of covariance and Bonferonni post hoc test Findings: By controlling the effect of age, there was a significant difference in the use of various defense mechanisms between veterans and normal people (p<0.01). The difference between the mean scores of using the mature and immature defense mechanisms was significant in the two groups (p<0.01). Veterans used more immature defense mechanisms than normal people and used less mature defense mechanisms. There was no significant difference between the mean scores of neurotic defense mechanisms in the two groups (p>0.05). Conclusion: Veterans use more mature and immature defense mechanisms than normal people, but they do not differ in the use of neurotic defense mechanisms.